2017
DOI: 10.1007/s00216-017-0342-6
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids for the passive sampling of sulfonamides from water—applicability and selectivity study

Abstract: Ionic liquids (ILs) are new-generation, non-volatile solvents which are designable, and their structure may be specifically adjusted to the current application needs. Therefore, it is possible to create and apply ILs which efficiently and selectively extract various analytes from different matrices. It has already been examined that ILs may be applied as receiving phases in passive sampling for the long-term water monitoring of PAHs and pharmaceuticals in water. In this paper, the concept of passive sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Furthermore, these compounds have a second dissociation constant, reflecting the ionization of the sulfonamide group, and the presence of anions at a pH higher than 5.9‐8.4, depending on the compound (). The specific dissociation reactions are presented in our previous publication . It can be assumed that the anionic forms of these compounds, which are present at pH 9, are preferentially soluble in water than adsorbed in HLB‐type sorbent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these compounds have a second dissociation constant, reflecting the ionization of the sulfonamide group, and the presence of anions at a pH higher than 5.9‐8.4, depending on the compound (). The specific dissociation reactions are presented in our previous publication . It can be assumed that the anionic forms of these compounds, which are present at pH 9, are preferentially soluble in water than adsorbed in HLB‐type sorbent.…”
Section: Resultsmentioning
confidence: 99%
“…It was assumed that good wettability and a high pore size had no impact on the pharmaceutical diffusion. In our previous study, the adsorption of pharmaceuticals onto the PES membrane was negligible [20]. The factor which can lower the EE results is the desorption of pharmaceuticals from the HLB sorbent by methanol.…”
Section: The Limitation Of the Study And Comparison With Other Studiesmentioning
confidence: 99%
“…The calculated time-weighted average concentration for most analytes was consistent with that obtained from active sampling. The obtained results contributed to the creation of further studies on the development of POCIS-like samplers with ionic liquids (Męczykowska et al 2017b(Męczykowska et al , 2018(Męczykowska et al , 2019.…”
Section: Innovative Sorbentsmentioning
confidence: 77%
“…Tang and his team carried out the extraction of two antibiotic drugs, ciprofloxacin and levofloxacin, using fatty acid/alcohol-based HDESs via the liquid–liquid microextraction method. Both ciprofloxacin and levofloxacin are commonly used as therapeutic and preventative antimicrobial medicines in aquaculture and animal husbandry. , They found that 1-octanol:methyltriooctylammonium chloride (1:1) showed the highest extraction efficiency. In addition, the study demonstrated that when compared to ultrasound, heating, and microwave techniques, the vortex-assisted procedure was the most effective way for extracting ciprofloxacin and levofloxacin.…”
Section: Applications Of Hdessmentioning
confidence: 99%